The effects of plyometric hurdle hopping and box jump training against men's ability - Kholiq, Nur; Wicaksono, Lungit; Sumantri, Riyan Jaya; Siswoyo, Joan (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to determine the effect of hurdle hopping and box jump exercises on men's volleyball smash skills in extracurricular students of SMK YPI Tanjung Bintang in South Lampung Regency. The research method used in this study is an experiment with the aim of finding out whether the study results affect the problem being studied. The sample of this study is students who participated in extracurricular volleyball exercises at SMK YPI Tanjung Bintang totaling 30 students. The sampling technique used ordinal pairing with a division of 2 groups, namely the hurdle hopping and box jump groups. The instrument used measured the smash ability of extracurricular volleyball athletes in schools. The results of the study showed that 1) There was a significant influence of plyometric hurdle hopping practice on smash ability in the volleyball team of SMK YPI Tanjung Bintang, with a value of sig (2-tailed) 0.00 < 0.05. 2) There was a significant influence of plyometric box jump practice on the ability of smash in the volleyball team of SMK YPI Tanjung Bintang, with a value of sig (2-tailed) 0.00 < 0.05. 3) there was The difference between the Plyometric Hurdle Hopping and Plyometric Box Jump training exercises is significant to the smash ability of the volleyball team of SMK YPI Tanjung Bintang, with a sig (2-Tailed) value of 0.002 < 0.05, it can be concluded that there is a significant difference and the value in the mean hurdle hopping group gets a value of 13.67 while the box jump group gets a value of 15.27 greater than group hurdle hopping.